Answer:
Step-by-step explanation:
im pretty sure its this smack me if im wrong
for 6
in a
given
slope(m)=1
point=(2,-4)=(x1,y1)
we know
equation of straight line
y-y1=m(x-x1)
y+4=1(x-2)
y+4=x-2
therefore x-y-6=0 is the required equation
substituting with ax+by+c=0 we get
a=1
b= -1
c= -6
Answer:
A, D, E
Step-by-step explanation:
<h3>
Answer: 5</h3>
=================================================
Explanation:
Let's consider the expression (x-y)^2. It expands out to x^2-2xy+y^2. The terms are:
Each of those terms either has a single variable with an exponent of 2, or has the exponents add to 2. Think of 2xy as 2x^1y^1.
In short, this means that the degree of each monomial term is 2.
----------
Now consider (x-y)^3. It expands out into x^3-3x^2y+3xy^2+y^3.
We have terms that either have a single variable and the exponent is 3, or the exponents add to 3. The degree of each term is 3.
----------
This pattern continues.
In general, for (x-y)^n, where n is any positive whole number, the degree of each term in the expansion is n. If you picked any term, added the exponents, then the exponents will add to n.
Answer:
2:3
Step-by-step explanation:
4:6
4/2=2
6/2=3